War on the Waters : The Union and Confederate Navies, 1861-1865 - McPherson, James M. (Book collections on Project MUSE., 2012)
Although previously undervalued for their strategic impact because the represented only a small percentage of total forces, the Union and Confederate navies were crucial to the outcome of the Civil War. In War on the Waters, James M. McPherson has crafted.